Metal-Mediated Halogen Exchange in Aryl and Vinyl Halides: A Review - Evano, Gwilherm; Nitelet, Antoine; Thilmany, Pierre; Dewez, Damien F. (Frontiers in Chemistry, 2018)
Halogenated arenes and alkenes are of prime importance in many areas of science, especially in the pharmaceutical, agrochemical and chemical industries. While the simplest ones are commercially available, some of them are still hardly accessible depending on their substitution patterns and the nature of the halogen atom. Reactions enabling the selective and efficient replacement of the halogen atom of an aryl or alkenyl halide by another one, lighter or heavier, are therefore of major importance since they can be used for example to turn a less reactive aryl/alkenyl chloride into the more reactive iodinated derivatives or, in a reversed sense, to block an undesired reactivity, for late-stage modifications or for the introduction of a radionuclide. If some halogen exchange reactions are possible with activated substrates, they usually require catalysis with metal complexes. Remarkably efficient processes have been developed for metal-mediated halogen exchange in aryl and vinyl halides: they are overviewed, in a comprehensive manner, in this review article.